The effect of preservatives and freezing on the morphological characters of two sparid fishes - Jawad, L A; Toumi, F F E L; Barasi, H M E L; Silini, O A E L (Indian Journal of Fisheries, 2011)
The effect of different concentrations of preservatives and freezing on somemorphological characters of the two sparid fish species, Boops hoops and Diplodusannularis was studied. Results revealed that different concentrations of formalinand alcohol on one hand and freezing on the other caused variable degrees ofshrinkage of the three characters studied.